Isolation and Identification of Microorganisms from High Vaginal Swab of Pregnant Women Visiting Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The primary objective was to isolate and identify the bacteria present in high vaginal swabs (HVS) of pregnant women and assess their antibiotic susceptibility patterns.Methods: A cross-sectional study was conducted between January and June 2024, involving 300 HVS samples collected from pregnant women attending Paropakar Maternity and Women’s Hospital (PMWH). The samples were cultured on Mac Conkey and Blood agar plates. Antibiotic susceptibility test of the identified bacterial colonies was carried out by Kirby Bauer disc diffusion method. Results: Of the 300 samples, 79 tested positive for bacterial growth, revealing a diverse range of organisms, with Escherichia coli (29.11%), Citrobacter koseri (22.79%), Proteus mirabilis (20.25%), and Klebsiella pneumoniae (17.72%) as the predominant species. The highest incidence of bacterial presence was observed in the 21-25 age group (35.44%).Conclusion: This study highlights the concerning prevalence of bacteria and their antibiotic resistance in HVS from pregnant women, underscoring the need for improved infection control measures and targeted antibiotic strategies.